Pengajaran kemahiran mendengar pada abad ke-21 (Teaching listening skills in the 21st century) / Wan Faizatul Azirah Ismayatim …[et al.] - Ismayatim, Wan Faizatul Azirah; Mohamad Nazri, Nur Dalila; Darmi, Ramiaida; Ab Wahab, Nursyuhada’; Zamri, Nur Adibah; Harun, Haliza; Abdullah, Hazlina; Md Yunus, Melor (Universiti Teknologi MARA, 2020)
This paper presents an innovation of a revolutionized self-directed English learning module entitled My Electronic Visual and Audio (MyEVO), which is designed and developed to assist language learners to conveniently acquire the required listening skills through the combination of current and stateof-the-art technology - a the module indicate that learners are very excited and happy to use technology assisted module in acquiring listening skills compared to the traditional module. Educators also believe that this module cater the needs of the 21st century learners and is suitable to be used inside the classroom or as a self-directed learning module. Another key feature of this smart module highlighted by the educators is the ability of the mobile application that allows learners to engage with the e-global community known as ‘MyEVO community, where all users can share their answers and exchange opinions regarding the given questions. In addition, listening activities that were designed in this module also cover the Higher Order Thinking Skills (HOTS) needed in learning. Educators also agreed that this interactive feature does not only encourage the learners to be active in their learning but it also helps to reduce their anxiety, learning process becomes more interesting and helps to aid their understanding of the topics covered.